Insights into frankincense and myrrh research: A comprehensive analytical study of patterns and perspectives - Siddig Ibrahim Abdelwahab; Manal Mohamed Elhassan Taha; Ahmed Ali Jerah; Abdullah Farasani; Saleh Mohammad Abdullah; Ieman A. Aljahdali; Omar Oraibi; Bassem Oraibi; Hassan Ahmad Alfaifi; Amal Hamdan Alzahrani; Yasir Osman Hassan Babiker (Heliyon, 2024)
Objective: Frankincense (Boswellia) and Myrrh (Commiphora) are natural substances that have a long history of traditional use and potential therapeutic applications. This study aimed to provide comprehensive insights into the literature on Frankincense and Myrrh research (FMR) by examining patterns, perspectives, and research trends within the research landscape. Methods: This bibliometric study utilized MeSH-generated terms, followed the PRISMA guidelines, and analyzed English-based bibliographic data from original studies retrieved from the Scopus database. The VOSviewer and Bibliometrix applications were employed to analyze the CVS and BibTex data consisting of 955 records. This study focuses on publication trends, research topics, citation counts, research impacts, and collaboration dynamics. Results: The analysis revealed a steady increase in FMR, indicating growing interest in these substances. Egypt, the United States, and Saudi Arabia are the most prolific countries in terms of research output. FMR primarily focuses on chemical composition, pharmacological properties, and medicinal applications. Key research topics include identification and analysis of bioactive compounds, optimization of extraction techniques, and evaluation of their therapeutic potential. Surprisingly, the thematic map was overwhelmed by the niche, motor, basic, and emerging themes. Trending topics in FMR include “Myrrh oil”, “sesquiterpene”, “tapping”, “triterpenoids”, and “allergic contact dermatitis”. Collaboration networks highlight the involvement of diverse stakeholders, indicating the importance of multidisciplinary and international collaboration in advancing the field. Conclusions: These insights contribute to a better understanding of the research landscape of FMR, guiding future studies and facilitating the utilization of these natural substances for the benefit of society.